2017
DOI: 10.3390/app7080844
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous InGaZnO Thin Film Transistor Fabricated with Printed Silver Salt Ink Source/Drain Electrodes

Abstract: Abstract:Recently, amorphous indium-gallium-zinc-oxide thin film transistors (a-IGZO TFTs) with inkjet printing silver source/drain electrodes have attracted great attention, especially for large area and flexible electronics applications. The silver ink could be divided into two types: one is based on silver nanoparticles, and the other is silver salt ink. Organic materials are essential in the formulation of nanoparticle ink as a strong disperse stabilizer to prevent agglomeration of silver particles, but wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…[ 168 ] When analyzed by electron energy loss spectroscopy (EELS), a silver salt‐based ink (TEC‐IJ‐010, INKTEC, Korea) was employed to fabricate inkjet‐printed Ag contacts that presented significantly less accumulation of carbon impurities at the interface of the Ag and IGZO semiconductor than was observed when devices were prepared using an Ag NP based ink (Figure 6c). [ 50 ] However, the generated Ag material exhibited a porous structure, which might compromise mechanical durability and lead to a collection of point‐like contacts to the semiconductor. In another study investigating the same Ag ink versus sputtered Ag, [ 12 ] the bulk of the printed Ag material was also observed by transmission electron microscopy (TEM) to be porous, but there appeared to be an intimate contact for charge injection between IGZO and Ag.…”
Section: Methodsmentioning
confidence: 99%
“…[ 168 ] When analyzed by electron energy loss spectroscopy (EELS), a silver salt‐based ink (TEC‐IJ‐010, INKTEC, Korea) was employed to fabricate inkjet‐printed Ag contacts that presented significantly less accumulation of carbon impurities at the interface of the Ag and IGZO semiconductor than was observed when devices were prepared using an Ag NP based ink (Figure 6c). [ 50 ] However, the generated Ag material exhibited a porous structure, which might compromise mechanical durability and lead to a collection of point‐like contacts to the semiconductor. In another study investigating the same Ag ink versus sputtered Ag, [ 12 ] the bulk of the printed Ag material was also observed by transmission electron microscopy (TEM) to be porous, but there appeared to be an intimate contact for charge injection between IGZO and Ag.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several types of silver inks were inkjet-printed on IGZO thin film for completing TFTs, and it was found that Ag salt ink is much better than Ag nanoparticle ink to produce high-performance TFTs. The IGZO TFTs with printing Ag S/D electrodes showed a mobility of 4.28 cm 2 V –1 s –1 and an I on / I off of 10 6 . Meanwhile, some approaches were proposed for fabricating short channels with printing electrodes.…”
Section: Printed Tfts On Rigid Substratementioning
confidence: 99%
“…The IGZO TFTs with printing Ag S/ D electrodes showed a mobility of 4.28 cm 2 V −1 s −1 and an I on / I off of 10 6 . 136 Meanwhile, some approaches were proposed for fabricating short channels with printing electrodes. Tang et al fabricated inkjet-printed Ag S/D electrodes with accurate control and produced the short channels with the width down to 20 μm by controlling ink wetting on a PVA surface, leading to form good interface contacts between organic semiconductor and electrodes (Figure 8b, c).…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…Conductive electrodes are of paramount importance for electronic devices because they provide effective electrical contacts for various functional components. Vacuum deposition is conventionally used for making electrode patterns. Compared to this method, inkjet printing could significantly reduce cost, save consumables, and improve production efficiency, therefore, printing is highly desirable for commercial mass production. , However, printing high-quality conductive patterns is still a challenge because the flow field inside the liquid film is a complex process.…”
Section: Introductionmentioning
confidence: 99%